KEBIJAKAN EKONOMI GLOBAL DINEGARA SEDANG BERKEMBANG: Tinjauan Teori, Problematika dan Interaksi Kebijakan Perdagangan dan Industrialisasi - Suharto, Toto (Universitas Muhammdaiyah Surakarta, 2002)
It is generally speaking that a country must consider industrial and trade sector in making its global economical policies, as both of them are significant role to supporting national economic growth. According to the writer, when we discuss about experiences in the case of implementing industrial and trade policies in the developing countries, there are three dominant perspective analysis as written in the developmental literature, namely Neoclassical perspective, Structural perspective and Radical perspective. Furthermore, the problem in the industrial and trade policies mostly occurs on three main issues, those are exporting policy, importing policy, and strategic options of industrialization which lies on between import substituting industry or export promoting industry. In this paper, the writer also analyzing economical globalization issue as a big challenge nowadays and proposing strategic anticipatory actions that the developing countries should prepare.